2014
DOI: 10.1073/pnas.1403697111
|View full text |Cite
|
Sign up to set email alerts
|

Detection of brown adipose tissue and thermogenic activity in mice by hyperpolarized xenon MRI

Abstract: The study of brown adipose tissue (BAT) in human weight regulation has been constrained by the lack of a noninvasive tool for measuring this tissue and its function in vivo. Existing imaging modalities are nonspecific and intrinsically insensitive to the less active, lipid-rich BAT of obese subjects, the target population for BAT studies. We demonstrate noninvasive imaging of BAT in mice by hyperpolarized xenon gas MRI. We detect a greater than 15-fold increase in xenon uptake by BAT during stimulation of BAT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
110
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(113 citation statements)
references
References 44 publications
3
110
0
Order By: Relevance
“…[114] However, the detection of this tissue still remains a challenge, especially in humans, [115] where it is sparsely distributed and not easy to detect by standard MR techniques. In the paper by Branca et al, [23] a strong enhancement of the intensity of the xenon-dissolved phase signal was reported in mice inhaling HP 129 Xe right after stimulation of non-shivering thermogenic activity in BAT, an effect which was ascribed to the strong enhancement in blood flow to BAT. [116] Blood flow to this tissue during stimulation can reach values as high as 5 L/min/kg, [116] considerably reducing xenon wash-in rate and allowing it to reach an in-tissue concentration of 10s of mM.…”
Section: Xementioning
confidence: 92%
See 2 more Smart Citations
“…[114] However, the detection of this tissue still remains a challenge, especially in humans, [115] where it is sparsely distributed and not easy to detect by standard MR techniques. In the paper by Branca et al, [23] a strong enhancement of the intensity of the xenon-dissolved phase signal was reported in mice inhaling HP 129 Xe right after stimulation of non-shivering thermogenic activity in BAT, an effect which was ascribed to the strong enhancement in blood flow to BAT. [116] Blood flow to this tissue during stimulation can reach values as high as 5 L/min/kg, [116] considerably reducing xenon wash-in rate and allowing it to reach an in-tissue concentration of 10s of mM.…”
Section: Xementioning
confidence: 92%
“…The lipid-dissolved peak was shown to have a temperature-sensitive chemical shift (-0.2 ppm/°C), which enabled direct measurement of the increase in tissue temperature ( Figure 5) during non-shivering thermogenesis. [23] In addition, during non-shivering thermogenesis, a relative decrease of the lipid-dissolved phase peak was observed with respect to the cytoplasm/blood peak, yielding direct evidence of this tissue's oxidative metabolism of internal triglycerides. More recently, the feasibility of BAT detection in humans during a single breath hold of HP xenon was demonstrated, with validation by FDG-PET.…”
Section: Xementioning
confidence: 93%
See 1 more Smart Citation
“…An extensive literature now exists on pulmonary imaging with use of 129 Xe, which has proved to be a safe and effective tracer in humans (89). A recent study, moreover, reported the use of hyperpolarized 129 Xe gas to detect BAT activation, yielding a more than 15-fold increase in hyperpolarized xenon uptake within BAT during stimulation (90), which suggests that this approach represents a viable future approach for human BAT imaging. Intriguingly, use of the same agent to directly track BAT heat production by exploiting the temperature dependence of xenon chemical shift has been reported (90).…”
Section: State Of the Art: Imaging Of Brown Adipose Tissuementioning
confidence: 99%
“…A recent study, moreover, reported the use of hyperpolarized 129 Xe gas to detect BAT activation, yielding a more than 15-fold increase in hyperpolarized xenon uptake within BAT during stimulation (90), which suggests that this approach represents a viable future approach for human BAT imaging. Intriguingly, use of the same agent to directly track BAT heat production by exploiting the temperature dependence of xenon chemical shift has been reported (90). The excitement surrounding hyperpolarized MR imaging must, however, be tempered by acknowledgment that this remains an experimental technique.…”
Section: State Of the Art: Imaging Of Brown Adipose Tissuementioning
confidence: 99%